Combined economic and emission dispatch using improved particle swarm optimization - Ha Trieu Phu; Nguyen Minh Duc Cuong; Nguyen Trung Thang (Journal of Technical Education Science, 2017)
The paper presents the application of improved Particle Swarm optimization algorithm (IPSO) for solving combined economic and emission load dispatch (CEED) problems where transmission power losses are considered. The method is developed by modifying the several modifications on the conventional Particle Swarm optimization (CPSO) is aiming to improve the performance of the original one. In the IPSO, one best local particle has been used to generate new solution instead of using the global best paritical like the conventional method. IPSO is tested on two different systems with the transmission power losses. The performance of IPSO is evaluated by comparing obtained results with other existing algorithms available in the study. As a result, it can be concluded that the applied method outperforms others and are very strong for solving the CEED problem.